Guanylyl Cyclase A/cGMP Signaling Slows Hidden, Age- and Acoustic Trauma-Induced Hearing Loss - Marchetta, Philine; Möhrle, Dorit; Eckert, Philipp; Reimann, Katrin; Wolter, Steffen; Tolone, Arianna; Lang, Isabelle; Wolters, Markus; Feil, Robert; Engel, Jutta; Paquet-Durand, François; Kuhn, Michaela; et al. (Frontiers in Aging Neuroscience, 2020)
In the inner ear, cyclic guanosine monophosphate (cGMP) signaling has been described to facilitate otoprotection, which was previously observed through elevated cGMP levels achieved by phosphodiesterase 5 inhibition. However, to date, the upstream hormone receptor pathways eliciting cGMP production are unclear. Here, we show that mice with a genetic deletion of the gene encoding the cGMP generator guanylyl cyclase (GC)-A, the receptor for atrial and B type natriuretic peptides, display a greater vulnerability of hair cells to hidden hearing loss and noise- and age-dependent hearing loss. This vulnerability was associated with GC-A expression in spiral ganglia and outer hair cells (OHCs) but not in inner hair cells (IHCs). GC-A knockout mice exhibited elevated hearing thresholds, most pronounced for the detection of high-frequency tones. Deficits in OHC input-output function in high-frequency regions were already present in young GC-A-deficient mice, with no signs of accelerated progression of age-related hearing loss or higher vulnerability to acoustic trauma. OHCs in these frequency regions from young GC-A knockout mice exhibited diminished levels of KCNQ4 expression, which is the dominant K+ channel in OHCs, and decreased activation of poly (ADP-ribose) polymerase-1, an enzyme involved in DNA repair. Further, GC-A knockout mice had IHC synapse impairments and reduced amplitudes of auditory brainstem responses that progressed with age and with acoustic trauma, in contrast to OHCs, compared to GC-A wild-type littermates. We conclude that GC A/cGMP-dependent signaling pathways have otoprotective functions and GC-A deletion differentially contributes to hair cell damage in a healthy, aged, or injured system. Thus, augmentation of natriuretic peptide/GC-A signaling likely has potential to overcome hidden and noise-induced hearing loss as well as presbycusis.